Light microscope observations on the epididymis of paca (Agouti paca) - Schimming, Bruno Cesar [UNESP]; Machado, Márcia Rita Fernandes [UNESP]; Simões, Karina; Da Cruz, Claudinei [UNESP]; Domeniconi, Raquel Fantin [UNESP] (My University, 2013)
The features of paca epididymis, based on its appearance in light microscope, is described in this paper. The cellular population of the epithelial lining comprises principal cells, basal cells, apical cells, narrows cells, and hallo cells. The epididymis is divided in five distinct and continuous regions, Zone I, or initial segment, and zone II, are both localized into the head. Zone III comprises the distal head and all the body. Zones IV and V are restricted to the tail, in the proximal and distal cauda epididymis respectively. Each zone can be readily distinguished on the basis of morphological characteristics. The height of epididymal epithelium is greater in zone I. There is a progressive increase in the diameter of the tubular lumen through the different areas, with the maximum in the zone V. The presence of a high epithelium, and the virtual absence of sperm in zone I suggest fast transit of spermatozoa in this region. Zone V comprises the distal tail, has smaller epithelial lining, greater luminal diameter, shorter stereocilia than the other zones, and contains spermatozoa packed inside the lumen, that characterizes this zone as a place of sperm storage. The findings are compared with other reports in rodents and other domestic animals, to contribute to the understanding of epididymal morphophysiology. © 2013 Firenze University Press.
Keywords: Epididymis; Morphology; Paca; Rodents; animal; cytology; epididymis; epithelium cell; histology; male; microscopy; rodent; seminiferous tubule epithelium; spermatozoon; Animals; Epithelial Cells; Male; Microscopy; Rodentia; Seminiferous Epithelium; Spermatozoa